Pengaruh Kepemimpinan Pemberdayaan, Motivasi Kerja Dan Beban Kerja Terhadap Turnover Intention Karyawan PT Genah Yogyakarta - Hermanto, Fahri (Yayasan Lentera Avanya Nagari, 2024)
This research departs from the reality where PT. Genah experienced Turnover Intention the high one. Namely reaching 20.57% in 2023. In fact, the limit set by the company is 15% per year. Therefore, this study aims to examine the influence of training, motivation and compensation on Turnover intention employees at PT. Genah. The population studied included 67 employees, and sampling techniques were used purposive sampling, where samples are selected based on research criteria. The research instrument used a questionnaire. The analytical method used is multiple linear regression. The research results show that partially, the work motivation variable does not have a significant effect on Turnover intention. On the other hand, the empowerment leadership variable has a negative and significant effect on Turnover intention. The workload variable has a positive and significant effect on Turnover intention. Simultaneously, the three independent variables (leadership empowerment, work motivation, and workload) have a significant effect on the dependent variable (Turnover intention) at PT. Genah. The practical implications of this research are that it is hoped that this research can become a basis for evaluation for PT. Genah in improving the relationship between superiors and employees so that they can optimize work processes that are more effective and productive. Theoretically, it is hoped that this research can become a source of information and reference for future researchers.